(untitled) (Applied Biological Research, 2011)
A significant decrease in haemoglobin, packed cell volume, total erythrocyte count, mean corpuscular volume, mean corpuscular haemoglobin and biochemical indices [total serum protein, albumin, globulin, albumin-globulin (A:G) ratio and blood glucose] and serum trace minerals (copper, cobalt and iron) were observed in eight goats showing the symptoms of anaemia and emaciation. Blood examination of anaemic goats revealed microcytic hypochromic anaemia. The anaemic goats were treated with an iron preparation injection Feritas (Intas Pharmaceuticals Ltd., India) @ 1 ml per animal intra-muscularly. Second and third injection was repeated 3 days each after first dosing. Along with parenteral therapy the anaemic goats were also given Ayumin V5 mineral mixture (Dabur Ayurvet Pvt. Ltd., India) @ 10 g daily to each goat for 30 days to supplement the micronutrients. The therapeutic response to iron preparation with oral haematinics resulted in significant improvement in haemogram of goats suffering from anaemia. Total serum protein and blood glucose also increased significantly after treatment. Significant improvement in serum copper, cobalt and iron level was observed after treatment. It can be concluded that the use of oral and parentral haematinics is very effective in treating the nutritional anaemia in goats.